2015
DOI: 10.16965/ijar.2015.187
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Percutaneous Tibial Length With Body Height and Estimation of Stature in Living Central India Population

Abstract: Identification of an individual by estimation of stature has got medico-legal importance. In present study an attempt will be made to estimate the stature from percutaneous length of tibia. Study subject consists of 40 adult males and 40 adult females between the age group of 18-30 years, born in Central India. Simple regression formula was derived showing the correlation between percutaneous length of tibia and stature of an individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…In the present study, significant difference was observed in the length of the right and left tibia which disagrees with the study of Mehta et al (2015a). This is maybe due to differences in sample size, measuring instruments, and age group in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, significant difference was observed in the length of the right and left tibia which disagrees with the study of Mehta et al (2015a). This is maybe due to differences in sample size, measuring instruments, and age group in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar study was also carried out by Mehta et al (2015a) on 80 adults (40 males and 40 females) in the age group 18 to 30 years in central India (Mehta et al 2015b). This study concluded that there was a strong correlation between the height and tibial length in both sexes with R = 0.886 and R = 0.864 for the right tibial length and left tibial length respectively.…”
Section: Discussionsupporting
confidence: 60%
“…This was important more so because most Indian researchers had formulated single regression equation or multiplying factor taking both sexes together into account. 13,14 By comparing the squared standard error of males and females using an F test it was found that the computed F exceeded the critical F value. The null hypothesis was rejected and thus the regression coefficient of males was significantly (p <0.05) different from females.…”
Section: Discussionmentioning
confidence: 99%
“…For measurement of right and left percutaneous Tibial length (PCTL), standardized and commonly applied protocol 10 and techniques [11][12][13][14] were followed. The spreading caliper with accuracy of measuring up to 0.1 cm.…”
Section: Methodsmentioning
confidence: 99%